Peningkatan Hasil Belajar Siswa Pada Pembelajaran IPS Dengan Model NHT Di Kelas IV Sekolah Dasar - Aulia, Frima; Arwin, Arwin; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to describe the improvement of student learning outcomes in learning IPS Using Coperative Learning Model Type Numbered Heads Together (NHT) in class IV SD Negeri 17 Java Gadut Padang City. Research subjects were teachers (practitioners) and 16 students. The place of study is SD Negeri 17 Jawa Gadut. The results showed an increase from cycle I to cycle II on: (a) Observation of RPP 87.5% (B) to 96.4% (SB). (b) Teacher aspect at 71.5% (C) to 90.9% (SB). (c) Aspects of learners 71.5% (C) to 90.9% (SB). (d) Student learning outcome 73,52% (C) becomes 91,39% (A).